2021
DOI: 10.1016/j.jds.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Review of oral ulcerative lesions in COVID-19 patients: A comprehensive study of 51 cases

Abstract: Numerous oral manifestations of COVID-19 have been reported in the literatures. Common oral lesions in COVID-19 patients included ulcerations, xerostomia, dysgeusia, gingival inflammation, and erythema. Among them, oral ulceration is the most frequent finding and is present as various but distinct patterns. Thus, we conducted a comprehensive review of 51 COVID-19 patients with oral ulcerative lesions to further analyze the various oral ulcerative lesions in COVID-19 patients. There were a median age of 41.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(64 reference statements)
1
21
0
3
Order By: Relevance
“…The oral symptoms of COVID-19 at the hospitalisation were limited to dysgeusia, which was observed in 17 patients (11%). During the period of hospitalisation, only two patients developed superficial ulcerative lesions covered with fibrinopurulent exudate surrounded by an erythematous halo, resembling aphthous-like ulcers [ 6–13 , 14 . One of these patients was HIV-positive, and as previously mentioned, also presented pseudomembranous candidiasis due to a marked decrease in the count of CD4 + T lymphocytes that relapsed after one week of hospitalisation when the ulcers also appeared.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The oral symptoms of COVID-19 at the hospitalisation were limited to dysgeusia, which was observed in 17 patients (11%). During the period of hospitalisation, only two patients developed superficial ulcerative lesions covered with fibrinopurulent exudate surrounded by an erythematous halo, resembling aphthous-like ulcers [ 6–13 , 14 . One of these patients was HIV-positive, and as previously mentioned, also presented pseudomembranous candidiasis due to a marked decrease in the count of CD4 + T lymphocytes that relapsed after one week of hospitalisation when the ulcers also appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies investigated the presence of HSV-1 by using serology tests [ 6 ], immunohistochemistry [ 13 ], saliva PCR assay [ 7 , 14 ] or lesion swab [ 9 ]. Although some cases were positive for HSV-1 [ 7 , 14 ], they maintained the possibility of a direct relationship with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the ulcer was the lesion more commonly reported and tongue the main anatomical area described by authors. Previous review [34] found a slight predisposition to the appearance of ulcers in patients with COVID-19, suggesting as a potential pathognomonic sign for early diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 88%